Hepatitic Variant of Graft-vs-Host Disease: Prevalence and Comparison With Clinicopathologic Features of the Classic Variant. Issue 6 (17th January 2022) - Liang, Tom Z; Dong, Stephen; Fang, Mike; Gong, Yuna; Yaghmour, George; Chopra, Shefali
Abstract: Objectives: Graft-vs-host disease (GVHD) of the liver is a complication of allogeneic hematopoietic stem cell transplantation with hepatitic and classic variants. We determined the percentage of hepatitic variant cases, compared clinicopathologic features of the two groups, and assessed prognostic factors. Methods: Fifty liver biopsy specimens from 40 patients with GVHD were studied. Results: Fifteen (30%) cases had moderate to marked lobular inflammation and were classified as a hepatitic variant. Bile duct damage was present in all cases. Ductular reaction, apoptosis. and endotheliitis were more commonly seen in the hepatitic variant. Hepatocyte ballooning was an independent poor prognostic factor. The median aspartate aminotransferase and alanine aminotransferase were higher in the hepatitic variant while alkaline phosphatase and bilirubin were higher in the classic group. Forty (80%) GVHD cases were more than 100 days after transplant, correlating to immunosuppression taper. There was response to treatment with increased immunosuppression in both groups, but time to normalization of liver function tests was higher in the hepatitic variant. Conclusions: Bile duct damage was the most consistent pathologic finding in our cohort and was present in all cases of GVHD. Moderate to marked lobular inflammation can be seen in GVHD in up to 30% of cases without any other coexisting cause. Hepatocyte ballooning is an independent poor prognostic factor.